Governance failure and youth unemployment levels in Nigeria (Alternate Horizons, 2022)
The Nigerian government has shied away from serving the youth's interests. At both the national and municipal levels, the powerful government officials who built vast patronage networks during the military era now use their political office to expand these networks and their fortunes dominate Nigerian politics. Nigeria's economic development and progress have suffered as a result of this. Nigeria's democratic consolidation efforts are hampered by persistent poverty, which is compounded by youth unemployment. A nation comprised of parasites, bandits, and beggars is doomed to fail. The youth's unemployment is related to an increase in sectarian criminality, terrorism, and violence. In addition, Nigeria's high youth unemployment level contributes to a high level of state insecurity, which leads to robberies, abductions, tribal tensions, arbitrary arrests, ethnoreligious conflicts, and other illicit activities in Nigeria. This article examines the relationship between governance failure and the youth unemployment level in Nigeria.